Analisis Sifat Dasar Sampah Anorganik (Plastik) Untuk Daur Ulang Menjadi Bahan Baku - David Setiawan; Rina Novia Yanti; Eteruddin, Hamzah (Politeknik Caltex Riau, 2023)
Nowadays, plastic waste has become a global issue on both the international and national levels, the same thing also occurred at the local level, including in Pekanbaru city. This cherished city has the potential to generate over 500 tonnes of rubbish every day, of which 14% is plastic waste. Even if it has a lesser volume than organic waste, the greatest concern is that it is difficult to digest by microorganisms in the soil, thus it can persist for a long period (10 – 500 years). Numerous initiatives have been made by scientists to reduce plastic waste. Among these, by employing the 3R principle, it can become something valuable. There are also people who try to convert it into building materials, including as paving stones and bricks. However, the final product retains its dull (dark) hue, making it less appealing. This research has established a process or method for melting plastic such that it can be used as a raw material for new goods while retaining its original hue.